2011
DOI: 10.1080/09593330.2010.523436
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the concentration of heavy metals associated with the sediment particles accumulated on road surfaces

Abstract: The heavy metal pollution caused by road run-off water constitutes a problem in urban areas. The metallic load associated with road sediment must be determined in order to study its impact in drainage systems and receiving waters, and to perfect the design of prevention systems. This paper presents data regarding the sediment collected on road surfaces in the city of Torrelavega (northern Spain) during a period of 65 days (132 samples). Two sample types were collected: vacuum-dried samples and those swept up f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 29 publications
1
26
0
7
Order By: Relevance
“…No obstante, los buques pesqueros, mercantes y cruceros turísticos emiten gran cantidad de partículas contaminantes que contienen MP. La contaminación se incrementa con el tráfico de vehículos que transportan la mercancía que llega al puerto, con el tránsito local y el tránsito por la carretera transpenisular que atraviesa la ciudad y corre a lo largo de la península de Baja California (Zafra, Temprano, & Tejero, 2011).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…No obstante, los buques pesqueros, mercantes y cruceros turísticos emiten gran cantidad de partículas contaminantes que contienen MP. La contaminación se incrementa con el tráfico de vehículos que transportan la mercancía que llega al puerto, con el tránsito local y el tránsito por la carretera transpenisular que atraviesa la ciudad y corre a lo largo de la península de Baja California (Zafra, Temprano, & Tejero, 2011).…”
Section: Introductionunclassified
“…However, fishing smack, merchant vessels and tourist cruise ships emit large amount of contaminant particles containing HM. Pollution increases with vehicle traffic carrying the goods that arrive at the port, with local and transpeninsular highway traffic through the city and along the peninsula of Baja California (Zafra, Temprano, & Tejero, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados mostraron que los modelos de tipo exponencial y potencial fueron los que mejores resultados produjeron (R 2 ≥0,84). Al respecto, Zhao y Li (19), Deletic y Orr (24), y Zafra et al (25) encontraron resultados similares. Es importante mencionar para la presente investigación, que esta fracción de tamaño fue la más cercana a la fracción potencialmente inhalable desde el punto de vista de la salud pública (i.e., ≤10 µm) y, además, la más susceptible de ser suspendida por altas velocidades del viento o por la turbulencia inducida por el tráfico en las vías de investigación.…”
Section: Resultsunclassified
“…However, these variations are found to be influenced by particle characteristics as the pollutants are generally strongly bound to particles (Badin et al, 2008;Charlesworth and Lees, 1999;Sansalone and Buchberger, 1997b;Vaze and Chiew, 2004;Vaze and Chiew, 2002;Zafra et al, 2011). Several studies have reported the fact that pollutant adsorption by particles depends on their physical and chemical characteristics such as particle size, surface area, surface charge distribution, surface coatings and organic matter content (Gunawardana et al, 2013;Gunawardana, 2011;Khanal et al, 2014;Murakami et al, 2009;Sposito, 2008;Zhang et al, 2016).…”
Section: Variability In Pollutant Build-up and Wash-offmentioning
confidence: 94%